Felicity & Cordelia : a tale of two bunnies - Jahn-Clough, Lisa (Farrar, Straus and Giroux, 2010)
Felicity and Cordelia are best friends, but they are separated when Felicity wants to go on a hot air balloon trip and Cordelia does not want to accompany her.